Illegal Fishing Activities of the Run Zeng Vessel in Indonesia - Surakusumah, Regan Meganata; Imamulhadi, Imamulhadi; Oktivana, Davina (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
In the last four years, the number of illegal fishing cases in Indonesia has relatively increased. The government is still working hard to catch the perpetrators of fisheries crimes that roam Indonesian waters. The Ministry of Maritime Affairs and Fisheries (MMAF) reported that a Russian-flagged foreign fishing vessel named Run Zeng from China entered Indonesia's Exclusive Economic Zone (EEZ) to conduct illegal activities such as illegal, unreported and unregulated (IUU) fishing practices, the use of trawling, and the deactivation of the Automatic Identification System (AIS). International environmental law requires countries to comply with rights and obligations related to environmental protection at the global level, including the marine environment. This research aims to specifically highlight the analysis of the environmental aspects of international law against the illegal activities of the Run Zeng vessel in Indonesia. By using normative juridical research methodology, which emphasizes the analysis of library materials in the form of secondary data. The results of this study indicate that the Run Zeng ship has carried out various illegal activities that violate the provisions of international conventions and laws and regulations in Indonesia. In law enforcement, Indonesia has adequate legal instruments to handle cases of environmental pollution by foreign vessels through bilateral agreements and national laws. This case has implications for Indonesia's commitment to realizing sustainable development in the marine and fisheries management sector, especially SDGs 14 Life Below Water through the concept of blue economy as outlined in the five priority programs of the MMAF.